2014
DOI: 10.3892/ijmm.2014.1808
|View full text |Cite
|
Sign up to set email alerts
|

Role of miR-146a in human chondrocyte apoptosis in response to mechanical pressure injury in vitro

Abstract: MicroRNA (miR)-146a is known to be overexpressed in osteoarthritis (OA). However, the role of miR-146a in OA has not yet been fully elucidated. In the present study, we applied mechanical pressure of 10 MPa to human chondrocytes for 60 min in order to investigate the expression of miR-146a and apoptosis following the mechanical pressure injury. Normal human chondrocytes were transfected with an miR-146a mimic or an inhibitor to regulate miR-146a expression. Potential target genes of miR-146a were predicted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 72 publications
3
97
0
1
Order By: Relevance
“…MiR146a was over-expressed in the chondrocytes model of experimentally induced human mechanical injury, accompanied by the up-regulation of VEGF and the down-regulation of Smad4 in vitro. miR-146a is involved in human chondrocytes apoptosis in response to mechanical injury and may contribute to the mechanical injury of chondrocytes as well as to OA pathogenesis by promoting VEGF expression and impairing the TGF-β signaling pathway through inhibiting Smad4 in cartilage [43]. Both of these studies confirmed the participation of the VEGF, Smad4 and TGF-β signaling pathway during the miR-146a-mediated OA pathology and discovered that Smad4 is the target of miR-146a in this process.…”
Section: Discussionmentioning
confidence: 99%
“…MiR146a was over-expressed in the chondrocytes model of experimentally induced human mechanical injury, accompanied by the up-regulation of VEGF and the down-regulation of Smad4 in vitro. miR-146a is involved in human chondrocytes apoptosis in response to mechanical injury and may contribute to the mechanical injury of chondrocytes as well as to OA pathogenesis by promoting VEGF expression and impairing the TGF-β signaling pathway through inhibiting Smad4 in cartilage [43]. Both of these studies confirmed the participation of the VEGF, Smad4 and TGF-β signaling pathway during the miR-146a-mediated OA pathology and discovered that Smad4 is the target of miR-146a in this process.…”
Section: Discussionmentioning
confidence: 99%
“…miR-146a was found to target and downregulate Smad4 , which subsequently induced VEGF expression and increased articular chondrocytes apoptosis. Another in vitro study using human articular chondrocytes has also shown that miR-146a is induced in chondrocytes by pressure-mediated mechanical stress [57]. This was accompanied by Smad4 downregulation, VEGF upregulation, and increased chondrocyte apoptosis.…”
Section: Role Of Microrna In Articular Cartilage Homeostasis and Ostementioning
confidence: 99%
“…6 The emerging role of miRNAs in OA is evident from studies comparing miRNA expression in both OA and normal articular tissues. miRNAs, including miR-140, 7,8 miR-320c, 9 miR-125b, 10 miR-27b, 11 miR-194, 12 miR-199a*, 13 miR-34a, 14 and miR-146a, 15 are implicated in various aspects of OA pathology, including regulating proteolytic enzymes, chondrocyte metabolism, and cartilage homeostasis and responding to the inflammatory microenvironment. Therefore, identification of the miRNAs regulatory network involved in OA is crucial for understanding its pathogenesis.…”
Section: Introductionmentioning
confidence: 99%